2011
DOI: 10.1007/s00238-011-0612-z
|View full text |Cite
|
Sign up to set email alerts
|

Breast reconstruction with polyurethane implants: preliminary report

Abstract: Today, immediate breast reconstruction is widely accepted in breast cancer surgery. There are many reconstruction procedures that combine cancer indications with patient's expectations. Improved techniques in the use of textured or polyurethane-coated implants and tissue expanders, associated with increasingly more conservative mastectomy procedures, may result in better cosmetic outcomes and less complications, even in patients that require postoperative radiotherapy. From June 2002 to December 2008, 166 unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Polyurethane coated breast implants provide a textured outer surface and have been researched recently due to the reported associated low capsular contracture incidence rates. A recent study by Pompei et al [ 54 ] looked at their use following radiotherapy, a recognised risk factor associated with capsular contracture. They found that capsular contracture occurred in 6.3% of patients who used polyurethane coated implants whereas those who had expanded textured implants inserted reported a rate of 21.7%.…”
Section: Strategies To Decrease the Incidence Of Capsular Contracturementioning
confidence: 99%
“…Polyurethane coated breast implants provide a textured outer surface and have been researched recently due to the reported associated low capsular contracture incidence rates. A recent study by Pompei et al [ 54 ] looked at their use following radiotherapy, a recognised risk factor associated with capsular contracture. They found that capsular contracture occurred in 6.3% of patients who used polyurethane coated implants whereas those who had expanded textured implants inserted reported a rate of 21.7%.…”
Section: Strategies To Decrease the Incidence Of Capsular Contracturementioning
confidence: 99%
“…Another retrospective study by Pompei et al [24] looked into the impact of radiotherapy on capsular contracture depending on the type of implant being used. Patient demographics, postoperative complications and cosmetic outcome were also recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Deflation-lipofilling sessions are conducted to prevent complications during the reconstructive step, limiting the onset of postoperative complications. As other authors promote the use of polyurethane implants as a first step in breast reconstruction to reduce complication rates [40,41] and not only as a rescue tool after a failure, in the same way, the present study investigated the beneficial effect of fat grafting as a part of the standard two-stage breast implant reconstruction for all postmastectomy patients in order to reduce overall capsular contracture and improve the esthetic result. This is the first report of 84 patients, a case-control study, with a mean follow-up time of 34.87 months.…”
Section: Discussionmentioning
confidence: 99%